Perancangan Sistem Informasi Penyewaan Rumah Pada Kontrakan Tunggal Abadi - Ibnu Yahya, Muslimin; Sani Wijaya, Ibnu; Setiawan, Roby (Jurnal Manajemen Teknologi Dan Sistem Informasi (JMS), 2025)
Kontrakan Tunggal Abadi is a provider of rental houses located on Jl. Batam Lrg. Tukang Jahit. Currently, data management for rentals is still using a ledger as a storage medium. Although the stored data is sufficient for now, searching for tenant data often encounters difficulties because all previous data must be manually reviewed. Additionally, the manual data processing through handwritten records causes various issues, such as difficulties in managing rental data, data storage, and data security. The risk of data loss is high, as everything is stored in a single ledger, and maintaining confidentiality is challenging due to limited access control. The purpose of this study is to analyze the existing system and design a more efficient rental house information system. The steps to be taken include identifying the problems, gathering information based on theoretical foundations, collecting data through observation and interviews, and analyzing the issues faced by Kontrakan Tunggal Abadi to find appropriate solutions. The system development will use the Waterfall model, with implementation in PHP and MySQL DBMS. The goal is to create an application that simplifies data processing and report generation, while also providing insights into the concepts of information system design for rental house administration based on web technology.